Rancang Bangun Sistem Informasi Manajemen Klinik Chania Care Center Berbasis Web Responsif - Putra, Galuh Dwi Agung; Rahmadi, Agyl Ardi; Armin, Aidil Primasetya (Jurnal Ilmu Siber dan Teknologi Digital, 2025)
Purpose: Technology has become an integral part of every aspect of life, including healthcare, including clinics. Technology plays a crucial role in addressing various challenges, such as patient management, pharmacy data management, and clinic management systems. Methodology/approach: The Chania Care Center Clinic implemented FEFO for efficient pharmacy inventory, ensuring older medications are used first, and used RAD methodology for iterative, rapid system design. Results/findings: Based on UMUX method testing, the admin role (2 respondents, average score 91.7) achieved an excellent (Grade A) usability rating. The doctor role (1 respondent, average score 79.1), pharmacy role (2 respondents, average score 75), and voter role (1 respondent, average score 83.3) all received a good (Grade C) usability rating. Conclutions: From this, it can be concluded that the Chania Care Center clinic system is well received by all users and all UMUX scores are in the “acceptable” category. Limitations: Despite these limitations, in developing the Chania Care Center clinic management information system, it is necessary to add a log of activities carried out by users so that from the log it can be monitored what activities users are carrying out on the system, so that security is well maintained. Contribution: This study details the creation of a responsive, user-friendly Chania Care Center clinic management system. It leverages the RAD (Rapid Application Development), FEFO (First Expired, First Out), and UMUX (Usability Metric for User Experience) methods to achieve its design and development goals.